The Rich World of p53 DNA Binding Targets: The Role of DNA Structure - Brázda, Václav (Int J Mol Sci, 2019)
The tumor suppressor functions of p53 and its roles in regulating the cell cycle, apoptosis, senescence, and metabolism are accomplished mainly by its interactions with DNA. p53 works as a transcription factor for a significant number of genes. Most p53 target genes contain so-called p53 response elements in their promoters, consisting of 20 bp long canonical consensus sequences. Compared to other transcription factors, which usually bind to one concrete and clearly defined DNA target, the p53 consensus sequence is not strict, but contains two repeats of a 5′RRRCWWGYYY3′ sequence; therefore it varies remarkably among target genes. Moreover, p53 binds also to DNA fragments that at least partially and often completely lack this consensus sequence. p53 also binds with high affinity to a variety of non-B DNA structures including Holliday junctions, cruciform structures, quadruplex DNA, triplex DNA, DNA loops, bulged DNA, and hemicatenane DNA. In this review, we summarize information of the interactions of p53 with various DNA targets and discuss the functional consequences of the rich world of p53 DNA binding targets for its complex regulatory functions.